Componential Study of the Chinese characters: the characteme and its didactic application to Spanish speakers - Chen, Hao; Liang, Quian (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Chinese writing system is different from European scripts. This is the fact which has increased the level of learning-teaching difficulty for Spanish-speaking students. Currently, the teaching of the Chinese characters’ components to foreign students, as well as academic research, has been considered very effective and insightful. However, as for the compositional study of Chinese characters, we have had several theories that are curiously based on different principles of the disassembly of Chinese characters, so it is necessary to rethink a unifying scientific term on the components to understand its connotations, in our case, the characteme. This article aims to introduce this new concept by the introduction of the study of Chinese character components as a starting point and, at the same time, to explain in a generic way its application in the teaching-learning of Chinese writing system and a reference for future scientific research in this regard.
Keywords: Bujian; characteme; chinese characters; teaching-learning; disassembly of components